Solidification Behavior of Ti-6Al-4V Alloy - Mitchell, Alec; Shirai, Yoshihisa; Kawakami, Akira; Mizukami, Hideo (ISIJ International, 2020)
It is important to understand the solidification behavior of titanium alloys for optimizing the casting conditions. In this study, to evaluate the solidification behavior of the Ti-6Al-4V alloy, an experiment was conducted using a lab-scale electron beam furnace. After melting the surface layer of the ingot through electron beam heating, the surface layer was allowed to solidify. Based on the measurement results of the cooling curve of the surface of the ingots, it was observed that the solid was subject to undercooling during its formation. The cooling rate of the ingot could be predicted through numerical simulation, for the melting and solidification of the ingot. The primary and the secondary dendrite arm spacing were examined with respect to the cooling rate. The concentrations of Al and V in the dendritic region were analyzed using electron probe microanalysis (EPMA). It is clarified that the Al is segregated into the dendrite core during solidification, and that V is segregated into the interdendritic region.